Beyond trees: Biogeographical regionalization of tropical Africa - Droissart, V.; Dauby, G.; Hardy, Olivier J.; Deblauwe, V.; Harris, D.J.; Janssens, S.; Mackinder, B.A.; Blach-Overgaard, A.; Sonke, B.; Sosef, M.S.M.; Stevart, T.; Svenning, Jens Christian; et al. (Wiley, 2018)
Aim To delineate bioregions in tropical Africa and determine whether different plant growth forms (trees, terrestrial herbs, lianas and shrubs) display the same pattern of regionalization, diversity and endemism as the whole flora.